REHYDRATION MECHANISMS IN COLLAGEN AS SEEN BY THERMALLY STIMULATED CURRENT - Nasser, Benrekaa (European Scientific Journal, ESJ, 2013)
The objective of this work is to suggest a quantitative model of natural skin aging. This model is expected to carry out tests for pharmaceutical or cosmetic products to achieve skin firmness purposes. We have defined an experimental protocol to highlight mechanism of rehydration and molecular mobility of collagen. Thermally stimulated currents in skin collagen have been investigated in the temperature range of -180°C to 60°C. We highlighted principally two types of molecular movements. α relaxation mode at approximately 20°C is associated with intermolecular mobility of tropocollagen molecules. Intermolecular mobility of polar sequences characterized by β relaxation mode is highly sensitive to hydration. This mode shows in the hydrated state two components: β1 and β2. During dehydration, there is firstly a significant decrease in the intensity of α and β1 modes and the disappearance of the β2 sub-mode. Finally, γ mode registered at -160°C is associated with non-polar amino acids.